Analisis Kesesuaian Lahan Untuk Tanamanan Porang (Amorphophallus Muelleri Blume) Dengan Berbagai Tanaman Naungan Di Kecamatan Bayan Kabupaten Lombok Utara - Sabariyah Sabariyah; Baharuddin Abubakar; IGM Kusnarta (Journal of Soil Quality and Management, 2023)
The Porang plant (Amorphophallus muelleri Blume) is one of the plants included in the ranks of superior food commodities that greatly support the economy of the people and the country. The purpose of this study was to determine the class of land suitability for Porang plants (Amorphophallus muelleri Blume), the class of land suitability for various shade crops, and the most suitable shade for Porang Plants in Bayan District, North Lombok Regency. This research was conducted using a descriptive method with survey techniques that included a series of basic map making activities and eight surveys. Data from field surveys and laboratory analysis were analyzed using the matching method. The results of this study show that the characteristics of the land in the research location of Porang planting land (Amorphophallus muelleri Blume) and Shade Plants in Bayan District, North Lombok Regency are included in the characteristics of land with a level of suitability between very appropriate (S1), quite appropriate (S2), marginal (S3), and not appropriate (N).